The drowned cities / 2. - Bacigalupi, Paolo (Ship Breaker, 2012)
In a dark future America that has devolved into unending civil wars, orphans Mahlia and Mouse barely escape the war-torn lands of the Drowned Cities, but their fragile safety is soon threatened and Mahlia will have to risk everything if she is to save Mouse, as he once saved her.